IT Infrastructure Automation Management with Infrastructure-As-Code (IAC) Modelling in Multi-Cloud Environments - Agus Sulaiman (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
Digital transformation has driven the adoption of multi-cloud environments, defined as the use of computing services from two or more public cloud providers (e.g., AWS, Azure, GCP) to mitigate vendor lock-in risks, optimize costs, and meet geographic requirements. However, multi-cloud environments pose significant management challenges, characterised by disparate API complexity, configuration discrepancies, and scalability bottlenecks that hinder rapid service delivery. This study aims to evaluate the effectiveness of Infrastructure-as-Code (IaC) modelling (using tools such as Terraform and Ansible) as a primary mechanism for automated management of IT infrastructure in complex multi-cloud architectures. The study uses a case study and experimental approach to compare metrics such as deployment time, configuration drift rate, and code portability when managing load balancers and distributed networks across three major cloud providers. The research hypothesis states that leveraging IaC, specifically platform-agnostic tools, significantly reduces operational overhead and improves infrastructure consistency (immutability) across different clouds compared to manual or console-based provisioning methods. The findings are expected to provide a practical framework and best practices for DevOps teams and Cloud engineers to achieve efficient automation and uniform governance in a multi-cloud ecosystem.